Analisis Prosedur Pembukaan Tabungan E-Mas melalui Platform BYOND By Bank Syariah Indonesia Ditinjau dari Prinsip Syariah dan Fatwa DSN-MUI - Dui Rafika Ramadhani; M. Masrukhan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study discusses the analysis of the account opening procedure for E-mas Savings through the digital platform BYOND by Bank Syariah Indonesia. The selection of this topic is motivated by the development of digital services in Islamic banking and the increasing public interest in gold investment products based on sharia principles. The purpose of this study is to identify the procedure for opening an E-mas Savings account and to examine its compliance with sharia accounting principles and DSN-MUI Fatwas. This research was conducted at Bank Syariah Indonesia KCP Tegal Sutoyo using data collection techniques in the form of observation, interviews, and documentation. The study employed a qualitative descriptive approach to obtain an in-depth understanding of the implementation of digital-based E-mas Savings services. The focus of the research was directed toward the stages of the account opening procedure, transaction mechanisms, and the application of sharia principles in digital banking services. The results indicate that the procedure for opening an E-mas Savings account has been implemented in accordance with applicable regulations and sharia principles, although there are still obstacles related to the uneven level of customer understanding regarding digital service mechanisms. In addition, the implementation of digital services through BYOND by BSI is considered capable of providing convenience, efficiency, and flexibility for customers in conducting gold investments without having to visit bank branches directly. Therefore, increased education and socialization for customers are needed so that the utilization of E-mas Savings can run more optimally and enhance public trust in digital-based sharia investment products.